Thyroid surgery for differentiated thyroid cancer — recent advances and future directions. Issue 11 (November 2018) - Wang, Tracy; Sosa, Julie
Abstract Population-based studies have demonstrated that an increasing number of incidental thyroid nodules are being identified. The corresponding increase in thyroid-based diagnostic procedures, such as fine-needle aspiration biopsy, has in part led to an increase in the diagnoses of thyroid cancers and to more thyroid surgeries being performed. Small papillary thyroid cancers account for most of this increase in diagnoses. These cancers are considered to be low risk because of the excellent patient outcomes, with a 5-year disease-specific survival of >98%. As a result, controversy remains regarding the optimal management of newly diagnosed differentiated thyroid cancer, as the complications related to thyroidectomy (primarily recurrent laryngeal nerve injury and hypoparathyroidism) have considerable effects on patient quality of life. This Review highlights current debates, including undertaking active surveillance versus thyroid surgery for papillary thyroid microcarcinoma, the extent of thyroid surgery and lymphadenectomy for low-risk differentiated thyroid cancer, and the use of molecular testing to guide decision-making about whether surgery is required and the extent of the initial operation. This Review includes a discussion of current consensus guideline recommendations regarding these topics in patients with differentiated thyroid cancer. Additionally, innovative thyroidectomy techniques (including robotic and transoral approaches) are discussed, with an emphasis on patient preferences around decision-making and outcomes following thyroidectomy. Small papillary thyroid cancers are considered low risk and account for the majority of incidental thyroid nodules. Here, Tracy S. Wang and Julie A. Sosa discuss the current debates and advances regarding the diagnosis and optimal treatment of differentiated thyroid cancer. Key points The incidence of thyroid cancer is increasing across the United States; this includes thyroid cancers of all tumour sizes and stages. Molecular testing for indeterminate thyroid nodules continues to evolve and guide recommendations for the extent of thyroid surgery. Appropriate extent of thyroidectomy for patients with low-risk thyroid cancer remains dynamic and might include active surveillance, thyroid lobectomy or total thyroidectomy. Given the excellent outcomes for most patients with differentiated thyroid cancer, patient preference and a robust discussion regarding options for the extent of surgery and long-term surveillance are critical. A strong association exists between surgeon volume and patient outcomes; surgeons' awareness of their own outcomes is critical. Referring providers, payers and policymakers should be aware of the implications of the association between surgeon volume and patient outcomes so that patient access to experienced thyroid surgeons can be optimized.